Signaling Peptides Regulating Abiotic Stress Responses in Plants - Kim, Jin Sun; Jeon, Byeong Wook; Kim, Jungmook (Frontiers in Plant Science, 2021)
As sessile organisms, plants are exposed to constantly changing environments that are often stressful for their growth and development. To cope with these stresses, plants have evolved complex and sophisticated stress-responsive signaling pathways regulating the expression of transcription factors and biosynthesis of osmolytes that confer tolerance to plants. Signaling peptides acting like phytohormones control various aspects of plant growth and development via cell-cell communication networks. These peptides are typically recognized by membrane-embedded receptor-like kinases, inducing activation of cellular signaling to control plant growth and development. Recent studies have revealed that several signaling peptides play important roles in plant responses to abiotic stress. In this mini review, we provide recent findings on the roles and signaling pathways of peptides that are involved in coordinating plant responses to abiotic stresses, such as dehydration, high salinity, reactive oxygen species, and heat. We also discuss recent developments in signaling peptides that play a role in plant adaptation responses to nutrient deficiency stress, focusing on nitrogen and phosphate deficiency responses.